2009
DOI: 10.1007/s12274-009-9021-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular flipping of an asymmetric tris(phthalocyaninato) lutetium triple-decker complex by scanning tunneling microscopy/spectroscopy

Abstract: The assembling behavior and electronic properties of asymmetric tris(phthalocyaninato) lutetium tripledecker sandwich complex molecules (Lu 2 Pc 3 ) on highly oriented pyrolytic graphite (HOPG) surfaces have been studied by scanning tunneling microscopy/spectroscopy (STM/STS) methods. Phase transitions were observed at different bias polarities, involving an ordered packing arrangement with fourfold symmetry at negative bias and an amorphous arrangement at positive bias. Molecular switching behaviour for indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Changes in the morphology induced by the STM tip were observed previously in molecular assemblies both at the solid/vacuum and liquid/solid interface. , Most examples refer to 180° flipping of nonplanar metal naphtalocyanines and noncentrosymmetric triple-decker complexes. In all these cases the molecules had a strong intrinsic molecular dipole that was flipping direction in order to align with the applied electric field. Instead, for BTB one possible scenario involves the molecules in solution being pushed away or aligned with the electric field depending on the polarization at the surface.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Changes in the morphology induced by the STM tip were observed previously in molecular assemblies both at the solid/vacuum and liquid/solid interface. , Most examples refer to 180° flipping of nonplanar metal naphtalocyanines and noncentrosymmetric triple-decker complexes. In all these cases the molecules had a strong intrinsic molecular dipole that was flipping direction in order to align with the applied electric field. Instead, for BTB one possible scenario involves the molecules in solution being pushed away or aligned with the electric field depending on the polarization at the surface.…”
Section: Resultsmentioning
confidence: 83%
“…The local electric field under a scanning tunneling microscope (STM) tip can be used to manipulate the diffusion and arrangement of atoms and molecules at the nanoscale. Because of strong intermolecular interactions that need to be reconfigured to manipulate the intermolecular connectivity landscape, it has been difficult to obtain reversible conformational switching in SAMs by means of electric fields. Accordingly, the systems studied so far included either metal–organic complexes with high intrinsic dipolar moments that can flip aligning to an external field or ionized species being adsorbed/desorbed or restructured from the solution in response to a charged interface. , Specially challenging is the possibility to find robust and reproducible systems that can keep the same response and reversibility after numerous switching cycles.…”
mentioning
confidence: 99%
“…Earlier works, reported on the use of a Scanning Tunneling Microscope (STM) to obtain images of supramolecular networks on appropriate conducting surfaces with sub-molecular resolution and on how to manipulate the surface arrangements of molecules and atoms. [16][17][18][19] In a previous work, we used the electric field between the tip of an STM and the sample as an external stimulus to locally manipulate the reversible transition between two different polymorphs of a single-component network at the solid-liquid interface 20 . We have shown that 1,3,5-tris(4-carboxyphenyl)-benzene (BTB) on Highly Oriented Pyrolytic Graphite (HOPG) undergoes an immediate transition from an open porous structure at negative bias to a close-packed polymorph at positive bias and viceversa (Fig.…”
mentioning
confidence: 99%